High-cycle fatigue behavior of Mg-8Li-3Al-2Zn-0.5Y alloy under different states - Xiang Peng; Xinli Liang; Wencai Liu; Guohua Wu; Hao Ji; Xin Tong; Liang Zhang; Wenjiang Ding (Journal of Magnesium and Alloys, 2021)
In this study, the tensile and high-cycle fatigue properties of as-cast, solid solution treated and as-extruded Mg-8Li-3Al-2Zn-0.5Y alloy are investigated. The results show that the yield strength and ultimate tensile strength of as-cast alloy is 198.1 MPa and 222.5 MPa, which are improved to 274.7 MPa and 321.7 MPa, 282.4 MPa and 319.3 MPa after solid solution and extrusion treatment, respectively. The high-cycle fatigue strength (at 107 cycles, R = -1) of as-cast studied alloy is 65 MPa, which is improved to 90 MPa and 105 MPa after solid solution and extrusion treatment, respectively. The improvement of fatigue property of the solid solution treated alloy is mainly due to the lattice distortion caused by solid solution hindering the crack propagation. However, the improvement of fatigue property of the as-extruded alloy is mainly due to that the refined grains, stacked dislocations and dispersed secondary particles impede the crack propagation.